LEGAL LANGUAGE IN DIGITAL MEDIA COVERAGE OF THE NURHADI CASE: A CRITICAL DISCOURSE ANALYSIS OF POLICE ACCOUNTABILITY AND INSTITUTIONAL LEGITIMACY - ARIFUDIN (Yayasan Pendidikan Aksara Cendikia, 2026)
This article examines the construction of legal discourse in online media coverage of the death of Brigadier Muhammad Nurhadi at Villa Tekek, North Lombok, allegedly resulting from abuse committed by his superior officers. Drawing on Norman Fairclough’s Critical Discourse Analysis (CDA), the study examines three interrelated dimensions: textual practice, discursive practice, and social practice. At the textual level, media framing relies on legalistic diction such as “suspect” and “investigation” that foregrounds procedural aspects of the case while obscuring substantive accountability. At the discursive practice level, the analysis reveals heavy media reliance on institutional sources, which reproduces police narratives while marginalizing the voices of the victim’s family and civil society. At the social practice level, the findings reveal asymmetrical power relations in which legal discourse functions to legitimize institutional authority rather than to encourage transparency. This research contributes to critical studies of legal language in journalism by illustrating how legal-bureaucratic discourse can simultaneously construct and obscure institutional accountability in cases of alleged state-apparatus violence.